Annual Report 1998-1999 (1999)
An administrative report of statistics and information pertaining to the University of North Florida Thomas G. Carpenter Library for the years 1998-1999.The report includes summaries and charts on library budgets, library collection, serials and cataloging workloads, circulation, interlibrary loan, and public services